Treating Acute Severe Eosinophilic Asthma with IL-5 Inhibitors in ICU - Nicolas Barbarot; Emmanuelle Nourry; Nicolas Massart; François Legay; Matthieu Debarre; Pierre Fillatre; Eric Magalhaes; Arnaud Mari; Julien Wallois; Eric Briens; Stéphane Jouneau (Case Reports in Pulmonology)
Introduction. About 10% of the 300 million people worldwide who suffer from asthma have a severe disease that is uncontrolled despite treatment with inhaled corticosteroids and long-acting beta agonists. The eosinophilic inflammation pathway in the respiratory tract and blood is involved and interleukin-5 (IL-5) has recently been identified as a major promotor of this pathway. The anti-IL-5 antibodies reduce the incidence of exacerbation and allowed steroid sparing in severe asthma patients but only two case reports have been published on their use in critical care. Case Presentation. This report describes the extraordinary clinical improvement of a young patient with steroid-refractory eosinophilic acute severe asthma who required mechanical ventilation, VV-ECMO followed by treatment with mepolizumab. The salient point in this case is the use of an anti-IL-5 monoclonal antibody for a critically ill patient whose condition was deteriorating despite mechanical ventilation and VV-ECMO. The usual steroid treatment failed to control the increase in blood eosinophils or his bronchial inflammation and constriction. Conclusion. Anti-IL-5 antibodies are now a standard treatment for severe eosinophilic asthma that can also be useful in an emergency to treat steroid-refractory eosinophilic acute severe asthma.